2016
DOI: 10.1063/1.4962202
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of GeO2/Ge and SiO2/Si structures on anomalous charging of oxide films upon water adsorption revealed by ambient-pressure X-ray photoelectron spectroscopy

Abstract: The energy difference between the oxide and bulk peaks in X-ray photoelectron spectroscopy (XPS) spectra was investigated for both GeO 2 /Ge and SiO 2 /Si structures with thickness-controlled water films. This was achieved by obtaining XPS spectra at various values of relative humidity (RH) of up to $15%. The increase in the energy shift is more significant for thermal GeO 2 on Ge than for thermal SiO 2 on Si above $10 À4 % RH, which is due to the larger amount of water molecules that infiltrate into the GeO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
(68 reference statements)
1
17
0
Order By: Relevance
“…Their shape (i.e., two chemical states with E bin = 33.3 and 34.3 eV due to Sb 3+ and Sb 5+ , respectively, with Sb–S environment) supports the discussion above on the Sb 3d 5/2 spectrum. , The Ge 3d spectrum revealed a single component at E bin = 30.9 eV. The latter binding energy refers to [GeS 4 ] 4– (30.8–30.9 eV) , and is much lower than that expected for GeO 2 (32.4–32.5 eV). , Thus, the presence of oxygenated Ge is rather unlikely.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Their shape (i.e., two chemical states with E bin = 33.3 and 34.3 eV due to Sb 3+ and Sb 5+ , respectively, with Sb–S environment) supports the discussion above on the Sb 3d 5/2 spectrum. , The Ge 3d spectrum revealed a single component at E bin = 30.9 eV. The latter binding energy refers to [GeS 4 ] 4– (30.8–30.9 eV) , and is much lower than that expected for GeO 2 (32.4–32.5 eV). , Thus, the presence of oxygenated Ge is rather unlikely.…”
supporting
confidence: 74%
“…The latter binding energy refers to [GeS 4 ] 4− (30.8−30.9 eV) 42,55 and is much lower than that expected for GeO 2 (32.4−32.5 eV). 56,57 Thus, the presence of oxygenated Ge is rather unlikely.…”
mentioning
confidence: 99%
“…While a number of APXPS studies have examined metal oxides in the presence of water vapor, only a few have reported a sharp onset to hydroxylation on the surfaces of Fe 3 O 4 (001), Al 2 O 3 /NiAl­(110), and MgO(100). , In all cases the sharp onset was observed at 10 –2 % RH. An in depth comparison of MgO(100) experiments to molecular simulations in the literature revealed mechanistic insight into the observed sharp onset in hydroxylation .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Herein we investigate the surface chemistry of ZnO(101̅0) for the first time using synchrotron-based ambient pressure XPS (APXPS). APXPS provides insight into how oxide surfaces interact with water vapor at pressures in the Torr range. , APXPS has been used to investigate the interaction of water vapor with various metal oxide surfaces under ambient conditions, including TiO 2 , SiO 2 /Si­(111), SiO 2 /Si­(100), Cu 2 O, Al 2 O 3 , α-Fe 2 O 3 (0001), MgO(100)/Ag(100), , Fe 3 O 4 (001), FeO/Au(111), Al 2 O 3 /NiAl­(110), GeO 2 /Ge­(100), , LaMO 3 perovskites, , LaCeO 2 (111), LiNbO 3 , and LaFeO 3 . Herein we report on results of isobar experiments performed at two different pressures (0.07 and 0.3 Torr) and temperatures from 295 to 750 K up to a maximum RH of 2%.…”
Section: Introductionmentioning
confidence: 99%
“…Even without GO/rGO sheets, the Ge surface was etched slowly in water. This is because dissolved O 2 molecules formed germanium dioxide (GeO 2 ) that absorbs water molecules , and is water-soluble . This natural etching has a rate of 0.46 nm/h at 22 °C, which increased slightly up to 6.2 nm/h at 58 °C.…”
Section: Resultsmentioning
confidence: 99%